Polymer latex containing vinylidene fluoride and trifluoroethylene

By controlling the polymerization conditions and using a specific fluorinated surfactant, VDF-TrFE copolymers achieve enhanced piezoelectric, pyroelectric, and ferroelectric properties, addressing the limitations of existing emulsion polymerization methods and safety concerns.

JP7612328B2Active Publication Date: 2025-01-14SOLVAY SPECIALTY POLYMERS ITALY SPA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2019517887
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-10-05
Filing Date
2017-09-29
Publication Date
2025-01-14
Estimated Expiration
2037-09-29

AI Technical Summary

Technical Problem

Existing methods for producing vinylidene fluoride (VDF) and trifluoroethylene (TrFE) copolymers through aqueous emulsion polymerization result in materials with poor piezoelectric, pyroelectric, and ferroelectric properties, and are associated with safety concerns due to high pressures and explosive behavior of TrFE.

Method used

A method involving the polymerization of VDF and TrFE in an aqueous emulsion using a specific fluorinated surfactant and a radical initiator, with controlled conditions to achieve a thermodynamically ordered structure, defined by the Xc(%) parameter, to enhance piezoelectric, pyroelectric, and ferroelectric performance.

Benefits of technology

The method produces VDF-TrFE copolymers with improved structural order, resulting in superior piezoelectric, pyroelectric, and ferroelectric performance, surpassing the properties of copolymers produced by alternative methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612328000029
    Figure 0007612328000029
  • Figure 0007612328000001
    Figure 0007612328000001
  • Figure 0007612328000002
    Figure 0007612328000002
Patent Text Reader

Abstract

The present invention provides a novel latex of vinylidene fluoride / trifluoroethylene copolymer particles that has a more ordered ferroelectric phase and therefore has improved ferroelectric, current collecting, and piezoelectric properties, and a method for preparing the latex by emulsion polymerization in the presence of certain cyclic fluorosurfactants. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application No. 16192408.9, filed October 5, 2016, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to novel latexes of copolymers of vinylidene fluoride and trifluoroethylene having improved ferroelectric properties, a process for their preparation in aqueous emulsions in the presence of specific fluorinated emulsifiers, and their use as piezoelectric, ferroelectric, dielectric or current collecting materials in electric / electronic devices. [Background technology]

[0003] Copolymers of vinylidene fluoride and trifluoroethylene have been exploited and developed for use in electrical / electronic devices (e.g., transducers, sensors, actuators, ferroelectric memories, capacitors) due to their ferroelectric, piezoelectric, current collecting and dielectric behavior / properties, with the piezoelectric behavior being particularly well known.

[0004] As is well known, the term piezoelectricity refers to the ability of a material to exchange electrical energy for mechanical energy and vice versa, and this electromechanical response is believed to be essentially related to dimensional changes during deformation or pressure oscillations. The piezoelectric effect is reversible in that materials that exhibit a direct piezoelectric effect (generation of electricity when stress is applied) also exhibit the inverse piezoelectric effect (generation of stress and / or strain when an electric field is applied).

[0005] Ferroelectricity is the property of a material whereby it exhibits a spontaneous electric polarization whose direction can be switched between equivalent states by the application of an external electric field.

[0006] Pyroelectricity is the ability of certain materials to generate an electric potential when heated or cooled. Indeed, as a result of this change in temperature, positive and negative charges migrate to opposite ends (i.e. the material becomes polarized) and thus an electric potential is established.

[0007] The piezoelectric, current collecting, and ferroelectric properties in copolymers of vinylidene fluoride and trifluoroethylene are generally understood to be related to a particular crystal habit, the so-called ferroelectric or beta phase, in which the hydrogen and fluorine atoms are arranged to give the largest dipole moment per unit cell.

[0008] Said VDF-TrFE copolymers are known in the art and are described inter alia in U.S. Pat. No. 4,778,867 (PRIES SEYMOUR (US)) 18 / 10 / 1988, U.S. Pat. No. 4,708,989 (THOMSON CSF (FR)) 24 / 11 / 1987, U.S. Pat. No. 4,784,915 (KUREHA CHEMICAL IND CO LTD (JP)) 15 / 11 / 1988, U.S. Pat. No. 4,173,033 (DAIKIN IND LTD (JP)) 30 / 10 / 1979.

[0009] Generally speaking, the techniques for producing these VDF-TrFE copolymers may be based on suspension polymerization, that is, using organic initiators in an aqueous phase under conditions of temperature and pressure such that VDF is in the supercritical phase, producing a slurry of coarse particles that precipitate from the aqueous polymerization medium immediately after production. Nevertheless, suspension polymerization methods require high pressures, and are quite troublesome to handle at an industrial level, due to the safety concerns associated with operating TrFE under such harsh conditions, where TrFE is likely to suffer from explosive behavior. Since TrFE is considered to have deflagration / explosion behavior similar to tetrafluoroethylene (TFE), the opportunity to limit the polymerization pressure represents a considerable advantage in safety management.

[0010] Therefore, techniques based on aqueous emulsion polymerization have been considered because they allow production under milder conditions, and moreover, they provide stable dispersions of VDF-TrFE polymer particles at high throughputs with limited trifluoroethylene (TrFE) partial and total pressures, and have few environmental concerns.

[0011] Furthermore, the access to VDF-TrFE polymer latexes allows opening up opportunities for processing / modification into coating / casting techniques based on solvent-free methods, which are attracting more and more attention in the field.

[0012] However, VDF-TrFE copolymers obtained from latexes produced by prior art aqueous emulsion polymerization processes suffer from certain shortcomings, including, inter alia, insignificant piezoelectric, pyroelectric and ferroelectric performance, when compared to, for example, suspension polymerized VDF-TrFE copolymers.

[0013] Here, optimization of the piezoelectric, current collecting or ferroelectric effects requires maximizing the thermodynamic order of the ferroelectric phase to achieve improved piezoelectric, pyroelectric and ferroelectric performance with more structured crystalline domains, which is in contradiction to the results obtained by emulsion polymerization.

[0014] On the other hand, emulsion polymerization techniques using certain cyclic fluorinated surfactants for the polyaddition polymerization of fluorinated monomers are known.

[0015] US Patent Application Publication No. 2011160415 (SOLVAY SOLEXIS SPA) 30 / 06 / 2011 discloses a method for producing a fluoropolymer comprising the aqueous emulsion polymerization of one or more fluorinated monomers, the aqueous emulsion polymerization being carried out according to the following formula (I): TIFF0007612328000001.tif29161 [wherein X1, X2, and X3, which are equal to or different from each other, independently contain H, F, and optionally one or more catenary or non-catenary oxygen atoms; C 1~6(per)fluoroalkyl groups; L represents a bond or a divalent group; R F is a divalent fluorinated C 1~3 Y is a hydrophilic functional group selected from the group consisting of anionic functional groups, cationic functional groups, and nonionic functional groups. Examples of fluorinated monomers that can be polymerized using the cyclic fluorocompound according to formula (I) as an emulsifier include partially or fully fluorinated gaseous monomers, including fluorinated olefins such as tetrafluoroethylene (TFE), chlorotrifluoroethylene (CTFE), hexafluoropropylene (HFP), vinyl fluoride (VF), vinylidene fluoride (VDF), partially or fully fluorinated allyl ethers and partially or fully fluorinated alkyl or alkoxy-vinyl ethers.

[0016] Furthermore, US Patent Application Publication No. 2012283382 (SOLVAY SPECIALTY POLYMERS ITALY, SPA) 8 / 11 / 2012 relates to a process for the manufacture of a dispersion of vinylidene fluoride (VDF) thermoplastic polymer, said process comprising the steps of polymerizing VDF in an aqueous phase comprising: at least one surfactant selected from the group consisting of non-fluorinated surfactants and fluorinated surfactants having a molecular weight of less than 400; and at least one functional (per)fluoropolyether comprising at least one (per)fluoropolyoxyalkylene chain and at least one functional group. Vinylidene fluoride polymers are generally polymers consisting of (a') at least 60 mol%, preferably at least 75 mol%, more preferably 85 mol% vinylidene fluoride (VDF); and (b') optionally 0.1 to 15 mol%, preferably 0.1 to 12 mol%, more preferably 0.1 to 10 mol% of a fluorinated monomer different from VDF; the fluorinated monomers being vinyl fluoride (VF), chlorotrifluoroethylene (CTFE), hexafluoropropene (HFP), Preferably selected from the group consisting of tetrafluoroethylene (TFE), perfluoromethylvinylether (MVE), trifluoroethylene (TrFE) and mixtures thereof, especially including homopolymers of VDF, VDF / TFE copolymers, VDF / TFE / HFP copolymers, VDF / TFE / CTFE copolymers, VDF / TFE / TrFE copolymers, VDF / CTFE copolymers, VDF / HFP copolymers, VDF / TFE / HFP / CTFE copolymers. Fluorinated surfactants having low molecular weight are represented by the formula: TIFF0007612328000002.tif33161 [wherein X1, X2, and X3, which are equal to or different from each other, are independently selected from the group consisting of H, F, and C1-C6 (per)fluoroalkyl groups, optionally containing one or more catenary or non-catenary oxygen atoms; R F represents a divalent perfluorinated C1-C3 bridging group, L represents a bond or a divalent group, and Y represents an anionic functional group. The surfactant may satisfy the above.

[0017] Therefore, there remains a need in the art for VDF-TrFE materials that are prepared by emulsion polymerization under mild conditions and that have improved piezoelectric, pyroelectric and ferroelectric performance.

[0018] The invention described herein now provides materials and methods that meet these needs. Summary of the Invention

[0019] The present invention therefore provides: repeat units derived from vinylidene fluoride (VDF) in an amount of at least 60 mol %, based on the total moles of repeat units; - repeat units derived from trifluoroethylene (TrFE) in an amount of at least 18 mol %, based on the total moles of repeat units; - optionally with repeat units derived from at least one additional monomer different from VDF and TrFE; providing an aqueous latex comprising particles of a polymer [polymer (F)] comprising The polymer (F) has a thermodynamically ordered structure in a ferroelectric phase, so that (i) Parameter Xc (%) defined as follows: TIFF0007612328000003.tif23161[where ΔH c is the enthalpy associated with the Curie transition between the ferroelectric and paraelectric phases, determined in J / g in the second heating scan by DSC at a heating rate of 10 °C, and ΔH m is the enthalpy of fusion in J / g according to ASTM D3418; and (ii) the content of repeat units different from VDF, expressed in mole % relative to the total moles of repeat units, designated CM (mol %); and The relationship is the following inequality: Xc(%) ≧ a·CM(mol%) + b [wherein a=-1.10 and b=75.00, preferably the inequality: Xc(%) ≥ a' CM(mol%) + b' (wherein a'=-0.89 and b'=71.33) Meet the following.

[0020] The present invention further relates to a method for making the latex as already detailed, said method comprising the step of polymerizing, in an aqueous emulsion, vinylidene fluoride (VDF), trifluoroethylene (TrFE) and, optionally, at least one additional monomer different from VDF and TrFE, in the presence of a radical initiator and a fluorinated surfactant [surfactant (C)] satisfying formula (I): TIFF0007612328000004.tif31161 [wherein X1, X2, and X3, which are equal to or different from each other, independently contain H, F, and optionally one or more catenary or non-catenary oxygen atoms; C 1~6 (per)fluoroalkyl groups; L represents a bond or a divalent group; R F is a divalent fluorinated C 1~3 is a bridging group; and Y is an anionic functional group.

[0021] The Applicant has surprisingly found that by the method already detailed it is possible to reach, under gentle conditions and at high throughputs, VDF-TrFE latices with improved piezoelectric, pyroelectric and ferroelectric performance, measured using the Xc(%) parameter defined above, as a result of their improved structural / conformational order in the ferroelectric phase of the VDF-TrFE latices, in particular at relatively low TrFE partial and total pressures. [Brief description of the drawings]

[0022] [Figure 1]3 is a plot of the parameter Xc(%), (hereinafter also referred to as the order parameter of crystallinity) as a function of the comonomer content (mol%) for the lattice of polymer (F); Δ is representative of an embodiment according to the invention obtained from emulsion polymerization in the presence of a cyclic surfactant (I) and a radical initiator; ■ and * are representative of non-practical embodiments, more specifically ■ refers to a latex obtained from emulsion polymerization in the presence of a different fluorosurfactant and an organic initiator, while * refers to a latex obtained from emulsion polymerization in the presence of a different fluorosurfactant and an inorganic initiator. The dotted lines represent inequalities. Inequality: Xc(%)≧a·CM(mol%)+b, where a=-1.10 and b=75.00, and inequality: Xc(%)≧a'·CM(mol%)+b', where a'=-0.89 and b'=71.33.

[0023] Disclosure of the Invention The polymer (F) of the present invention generally contains 18 to 40 mol %, preferably 20 to 35 mol %, of repeating units derived from TrFE.

[0024] The polymer (F) of the present invention may further comprise repeat units derived from one or more fluoromonomers other than VDF and TrFE, such as, inter alia, hexafluoropropylene, tetrafluoroethylene, chlorotrifluoroethylene, or repeat units derived from one or more non-fluorinated monomers, such as, inter alia, (meth)acrylic monomers, more particularly, repeat units derived from at least one hydrophilic (meth)acrylic monomer (MA) of the following formula: TIFF0007612328000005.tif27161 (wherein R1, R2, and R3 are equal to or different from each other and are independently a hydrogen atom or a C1 to C3 hydrocarbon group, and R OH is a hydroxyl group or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group).

[0025] Non-limiting examples of hydrophilic (meth)acrylic monomers (MA) are in particular acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate; hydroxyethylhexyl (meth)acrylate.

[0026] The monomer (MA) is more preferably: formula: Hydroxyethyl acrylate (HEA) from TIFF0007612328000006.tif29161; formula: TIFF0007612328000007.tif33161, either 2-hydroxypropyl acrylate (HPA), formula: TIFF0007612328000008.tif28161 Acrylic acid (AA), - and mixtures thereof is selected from.

[0027] The polymer is advantageously: repeat units derived from vinylidene fluoride (VDF) in an amount of 60 mol% to 81 mol%, based on the total moles of repeat units; - repeat units derived from trifluoroethylene (TrFE) in an amount of 18 mol% to 39 mol%, based on the total moles of repeat units, and - optionally repeat units derived from at least one additional monomer different from VDF and TrFE in an amount of 0 to 5 mol % Includes.

[0028] Nevertheless, polymers consisting essentially of repeat units derived from VDF and TrFE are generally preferred.

[0029] Such polymers are typically: - 18 to 35 mol %, preferably 20 to 32 mol %, of repeating units derived from TrFE; and 65 to 82 mol %, preferably 68 to 80 mol %, of repeating units derived from VDF It essentially consists of:

[0030] The melt flow index (MFI) of the polymer (F) will be chosen by the person skilled in the art in relation to the processing technique chosen to obtain the final part (for example a film or sheet).

[0031] Nevertheless, it is generally understood that the polymer (F) will advantageously have an MFI, measured according to ASTM D1238 (230°C / 5Kg), of between 0.5 and 500 g / 10 min, preferably between 1 and 200 g / 10 min, more preferably between 2 and 10 g / 10 min.

[0032] As stated above, the latex of the present invention comprises particles of polymer (F) having a parameter Xc(%), i.e., the crystallinity order parameter, such that the aforementioned inequality is satisfied.

[0033] From a technological point of view, this crystallinity order parameter is a measure of the structural and conformational order of the ferroelectric phase; the higher the Xc parameter, the more structured and the more ordered the ferroelectric crystalline phase is.

[0034] As a result, polymer (F) from the latex of the present invention has improved ferroelectric performance resulting from the ferroelectric crystalline phase, and the higher structural order results in better ferroelectric performance over polymers from latexes that can be produced using prior art techniques.

[0035] The method for making the latex, as detailed above, comprises reacting vinylidene fluoride (VDF), trifluoroethylene (TrFE), and optionally at least one additional monomer different from VDF and TrFE, in an aqueous emulsion with a radical initiator and a compound represented by formula (I): The method includes a step of polymerizing in the presence of a fluorinated surfactant [surfactant (C)] that satisfies the formula (wherein the formula is as described above in detail).

[0036] In the formula (I), the anionic functional group Y is represented by the formula: TIFF0007612328000010.tif26161(in the formula, a is H, a monovalent metal (preferably an alkali metal) or a group of the formula -N(R' n ) 4 ammonium groups, where R' is equal or different at each occurrence. n is a hydrogen atom or C 1~6 represents a hydrocarbon group (preferably an alkyl group) It is preferred that the fluorine-containing polymer is selected from the group consisting of:

[0037] Most preferably, the hydrophilic functional group Y is a carboxylate of formula (3″) as detailed above.

[0038] According to a first embodiment of the present invention, the cyclic fluoro compound is represented by the following formula (II): TIFF0007612328000011.tif30161 (wherein X1, X2, X3, Y and R F have the same meaning as defined above) Meet the following.

[0039] More preferably, the cyclic fluoro compound is represented by the following formula (III): TIFF0007612328000012.tif32161 (in the formula, R F , X1, X2, X3, and X a have the same meaning as defined above) Meet the following.

[0040] According to a second embodiment of the present invention, the cyclic fluoro compound has the following formula (IV): TIFF0007612328000013.tif44161[where, R F and X a has the same meaning as above; X*1 and X*2, which are equal or different from each other, are independently a fluorine atom, -R' f -OR' f , where R' f is C 1~3 R is a perfluoroalkyl group; F1 is F or CF3, and k is an integer from 1 to 3. Meet the following.

[0041] Among these compounds, the cyclic fluoro compounds of formula (V) are as follows: TIFF0007612328000014.tif35161(in the formula, a has the meaning defined above), in particular X a Cyclic fluoro compounds in which is NH4 have been found to be particularly useful in the process of the present invention.

[0042] The polymerization pressure is therefore generally comprised between 10 and 40 bar, preferably between 15 and 35 bar, more preferably between 20 and 35 bar.

[0043] The skilled artisan will select the polymerization temperature taking into account, inter alia, the radical initiator used. The polymerization temperature is generally selected in the range of 60°C to 120°C, preferably 75°C to 120°C.

[0044] It is understood that while the choice of radical initiator is not particularly limited, those suitable for the process according to the invention are selected from among compounds capable of initiating and / or promoting polymerization.

[0045] Those skilled in the art will be familiar with the many initiators that are suitable for the process according to the invention.

[0046] Organic radical initiators can be used, including but not limited to the following: acetylcyclohexanesulfonyl peroxide; diacetylperoxydicarbonate; dialkylperoxydicarbonates such as diethylperoxydicarbonate, dicyclohexylperoxydicarbonate, di-2-ethylhexylperoxydicarbonate; tert-butylperneodecanoate; 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile; tert-butylperpivalate; dioctanoylperoxide; dilauroylperoxide; 2,2'-azobis(2,4-dimethylvaleronitrile); tert-butylazo-2-cyanobutane; dibenzoylperoxide; tert-butylper-2-ethylhexanoate; tert-butylpermaleate; 2,2'-azobis(isobutyronitrile); bis(tert-butylperoxy). C) Cyclohexane; tert-butylperoxyisopropyl carbonate; tert-butylperacetate; 2,2'-bis(tert-butylperoxy)butane; dicumyl peroxide; di-tert-amyl peroxide; di-tert-butyl peroxide; p-methane hydroperoxide; pinane hydroperoxide; cumene hydroperoxide; and tert-butyl hydroperoxide. Other suitable radical initiators include chlorocarbon and fluorocarbon acyl peroxides, such as trichloroacetyl peroxide, bis(perfluoro-2-propoxypropionyl) peroxide, [CF3CF2CF2OCF(CF3)COO]2, perfluoropropionyl peroxide, (CF3CF2CF2COO)2, (CF3CF2COO)2, {(CF3CF2CF2)-[CF(CF3)CF2O] m -CF(CF3)-COO}2 (wherein m=0 to 8), [ClCF2(CF2) n COO]2, and [HCF2(CF2) n COO]2 (wherein n=0 to 8); perfluoroalkyl azo compounds, such as perfluoroazoisopropane, [(CF3)2CFN=]2, R 〇 N=NR 〇 (In the formula, R 〇is a linear or branched perfluorocarbon radical having 1 to 8 carbons; a stable or hindered perfluoroalkane radical, such as the hexafluoropropylene trimer radical, [(CF3)2CF]2(CF2CF2)C ● Included are halogenated free radical initiators such as radical and perfluoroalkanes.

[0047] Redox systems containing at least two components that form a redox pair, such as dimethylaniline-benzoyl peroxide, diethylaniline-benzoyl peroxide, and diphenylamine-benzoyl peroxide, can also be used to initiate polymerization.

[0048] Inorganic radical initiators can also be used, including, but not limited to, the following: persulfates, such as sodium persulfate, potassium persulfate, or ammonium persulfate; permanganates, such as potassium permanganate.

[0049] Inorganic radical initiators as detailed above are preferred.

[0050] The radical initiator is advantageously included in a concentration ranging from 0.001 to 20 weight percent of the polymerization medium.

[0051] The polymerization can be carried out in the presence of a chain transfer agent. The chain transfer agent is selected from those known for the polymerization of fluorinated monomers, such as ketones, esters, ethers or aliphatic alcohols having 3 to 10 carbon atoms, such as acetone, ethyl acetate, diethyl ether, methyl-tert-butyl ether, isopropyl alcohol, etc.; chloro(fluoro)carbons having 1 to 6 carbon atoms, optionally containing hydrogen, such as chloroform, trichlorofluoromethane; bis(alkyl)carbonates (wherein alkyl has 1 to 5 carbon atoms), such as bis(ethyl)carbonate, bis(isobutyl)carbonate, etc. The chain transfer agent can be fed to the polymerization medium at the start, continuously or in discrete amounts (stepwise) during the polymerization, although continuous or stepwise feeding is preferred.

[0052] The present invention also relates to the use of the above mentioned polymer (F) as ferroelectric, piezoelectric, dielectric or current collecting material in electric / electronic devices.

[0053] Non-limiting examples of said devices are transducers, sensors, actuators, ferroelectric memories, capacitors, among others.

[0054] The polymer (F) is generally included in the device in the form of a substantially two-dimensional part (for example a film or sheet).

[0055] The film or sheet can be manufactured by standard techniques such as extrusion, injection molding, compression molding and solvent casting.

[0056] Said two-dimensional article may further be subjected to post-processing treatments, especially to enhance the ferroelectric, piezoelectric, dielectric or current collecting behavior, such as, for example, annealing, stretching, biorientation, and the like.

[0057] The two-dimensional article can be subjected to, among other things, a high poling electric field obtained by poling cycles to adjust the polarization, remnant polarization and maximum displacement current measured in the coercive field in real time by a high voltage and data acquisition computer controlled system. Embodiments of this process are described in ISNER-BROM, P., et al. Intrinsic Piezoelectric Characterization of PVDF copolymers: determination of elastic constants. Ferroelectrics. 1995, vol. 171, p. 271-279., BAUER, F., et al. Very high pressure behaviour of precisely-poled PVDF. Ferroelectrics. 1995, vol. 171, p. 95-102., and in U.S. Pat. No. 4,611,260 (DEUTSCH FRANZ FORSCH INST (FR)) 9 / 09 / 1986 and U.S. Pat. No. 4,684,337 (DEUTSCH FRANZ FORSCH INST (FR)) 4 / 08 / 1987, the disclosures of which are incorporated herein by reference.

[0058] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.

[0059] The present invention will now be described in more detail with reference to the following examples, whose purpose is merely illustrative and is not intended to limit the scope of the invention. EXAMPLES

[0060] Formula (V)(X a Example of emulsion polymerization in the presence of a cyclic surfactant (=NH4) and a radical initiator (according to the invention) - Method I1 Example 1 - Copolymer VDF-TrFE 70 / 30 (molar ratio) 3.5 L of demineralized water were introduced into a vertical autoclave made of AISI 316 steel, equipped with baffles and an agitator operating at 570 rpm. The temperature was then brought to the reaction temperature of 85° C., and once this temperature was reached, the X reaction mixture detailed above was added. a 50 g of a 34% w / w solution of a cyclic surfactant of formula (V), =NH4, in distilled water and VDF in such an amount that the pressure reached 6.9 bar absolute were introduced. A gaseous mixture of VDF-TrFE in a nominal molar ratio of 70 / 30 was then added via a compressor until a pressure of 30 bar absolute was reached. The composition of the gaseous mixture present at the head of the autoclave was analyzed by GC. At the start of the polymerization, it was found that the gas phase consisted of: 75.9% by mole of VDF, 24.1% by mole of TrFE. Then 50 ml of a solution of sodium persulfate (NaPS) in demineralized water at a concentration of 3% by volume were fed. The polymerization pressure was kept constant by feeding the above VDF-TrFE mixture, and when 500 g of the mixture had been fed, the feeding of the mixture was interrupted and the pressure was left to drop to 15 bar absolute, while keeping the reaction temperature constant. The reactor was then cooled at room temperature, the latex was discharged and frozen for 48 hours, the coagulated polymer was thawed, washed with demineralized water and dried at 80° C. for 48 hours.

[0061] Example 5 - Copolymer VDF-TrFE in 79 / 21 (molar ratio) The same procedure as in Example 1 was followed, but initially 7.75 bar absolute VDF was introduced and supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 79 / 21 until a set pressure value of 30 bar absolute was reached, providing an initial composition throughout: 80.9 mol % VDF, 19.1 mol % TrFE, and continuing the feeding of said mixture in order to maintain the set pressure value.

[0062] Example 6 - Copolymer VDF-TrFE at 80 / 20 (molar ratio) The same procedure as in Example 1 was followed, but initially 7.8 bar absolute VDF was introduced and supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 80 / 20 until a set pressure value of 30 bar absolute was reached, providing an initial composition throughout: 81.9 mol % VDF, 18.1 mol % TrFE, and continuing the feeding of said mixture in order to maintain the set pressure value.

[0063] Example 8 - Copolymer VDF-TrFE at 75 / 25 (molar ratio) The same procedure as in Example 1 was followed, but initially 6.9 bar absolute VDF was introduced and then supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 75 / 25 until a set pressure value of 30 bar absolute was reached, and the feeding of said mixture was continued in order to maintain the set pressure value.

[0064] Emulsion Polymerization Example in the Presence of PFPE Surfactant and (Comparative) Organic Initiator - Method CM1 Example 2C - Copolymer VDF-TrFE at 70 / 30 (molar ratio) In a vertical autoclave made of AISI 316 steel, equipped with baffles and an agitator operating at 570 rpm, 3.5 liters of demineralized water were introduced. The temperature was increased to a reaction temperature of 120° C. When this temperature was reached, 32.5 g of a microemulsion prepared according to example 1 of US Pat. No. 7,122,608 (SOLVAY SOLEXIS SPA) were introduced, as well as VDF in such an amount that a pressure of 6.9 absolute bar was reached. A gaseous mixture of VDF-TrFE in a nominal molar ratio of 70 / 30 was then added via a compressor until a set pressure value of 30 absolute bar was reached. At the start of the polymerization, the gas phase was found by GC analysis to consist of 77.7 mol % VDF, 22.3 mol % TrFE. Then, 22 cc of pure di-tert-butyl peroxide (DTBP) was metered in, and the set pressure was kept constant by feeding the above VDF-TrFE mixture, a 2% mixture (target set at 288 g) was fed, and the temperature was lowered to 105° C. At the point where 288 g had been fed, the monomer feed was interrupted and the pressure was left to drop to 15 absolute bar while maintaining the temperature. The reactor was then cooled at room temperature, the latex was discharged and frozen for 48 hours, and the coagulated polymer was thawed, washed with demineralized water and dried at 80° C. for 48 hours.

[0065] Example 3C - Copolymer VDF-TrFE-AA in molar ratio 69.5 / 30 / 0.5 The same procedure as in Example 2C was followed, but the polymerization was carried out while continuing to feed said VDF-TrFE mixture, by supplementing the gaseous mixture of VDF-TrFE in a nominal molar ratio of 70 / 30 until the set pressure value of 30 absolute bar was reached, providing an initial composition throughout of 76.1 mol% VDF, 23.9 mol% TrFE, feeding 19 mL of DTBP in combination with an initial amount equal to 4 mL of an aqueous acrylic acid solution of 2.5 vol / volume, and feeding stepwise an amount of 4 mL of an aqueous acrylic acid solution of 2.5 vol / volume for every 29 g of monomer mixture consumed, to maintain the set pressure value, as detailed in Example 2C.

[0066] Example 7c--Copolymer VDF-TrFE at 80 / 20 (molar ratio) The same procedure as in Example 2C was followed, but initially 7.85 bar absolute VDF was introduced and supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 80 / 20 until a set pressure value of 30 bar absolute was reached, giving an initial composition throughout: 86.5 mol % VDF, 13.5 mol % TrFE, and 24 mL of DTBP was fed and the feeding of said VDF-TrFE mixture was continued in order to maintain the set pressure value.

[0067] Example 9c - Copolymer VDF-TrFE-AA in molar ratio 74.55 / 25 / 0.5 The same procedure as in Example 2C was followed, but initially 7.35 bar absolute VDF was introduced, supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 75 / 25, until a set pressure value of 30 bar absolute was reached, giving an initial composition throughout: 82.5 mol % VDF, 17.5 mol % TrFE, 30 mL of DTBP was fed in combination with 4 mL of the same acrylic acid solution as above, and the feeding of said VDF-TrFE mixture, said acrylic acid solution was continued in order to maintain the set pressure value, as detailed in Example 3C.

[0068] Example 11c--Copolymer VDF-TrFE in 75 / 25 (molar ratio) The same procedure as in Example 2C was followed, but initially 7.35 bar absolute VDF was introduced and supplemented with a gaseous mixture of VDF-TrFE in a nominal molar ratio of 75 / 25 until a set pressure value of 30 bar absolute was reached, giving an initial composition throughout: 82.5 mol % VDF, 17.5 mol % TrFE, and 27 mL of DTBP was fed and the feeding of said VDF-TrFE mixture was continued in order to maintain the set pressure value.

[0069] Emulsion Polymerization Example in the Presence of PFPE Surfactant and (Comparative) Inorganic Initiator - Method CM2 Example 10c - Copolymer VDF-TrFE in 75 / 25 (molar ratio) 3.5 L of demineralized water were introduced into an AISI 316 steel horizontal autoclave equipped with baffles and agitator operating at 570 rpm. The temperature was increased to a reaction temperature of 85° C. When this temperature was reached, 32.5 g of a microemulsion prepared according to example 1 of US Pat. No. 7,122,608 (SOLVAY SOLEXIS SPA) and 7.35 absolute bar of vinylidene fluoride were introduced. A gaseous mixture of VDF-TrFE in a nominal molar ratio of 75 / 25 was added via a compressor until a set pressure value of 30 absolute bar was reached. The gas phase was found to consist by GC: 82.2 mol % VDF, 17.8 mol % TrFE. Then, by means of a metering system, 60 mL of an aqueous solution of ammonium persulfate (1% by weight) was introduced. The polymerization pressure was kept constant by feeding the above-mentioned monomer mixture; the temperature was reduced to 105° C. when a 2% mixture (target set at 288 g) was fed. After 288 g had been fed, the feed was interrupted and the pressure was allowed to drop to 15 absolute bar whilst the temperature was kept constant. The reactor was allowed to cool at room temperature, the latex was discharged and frozen for 48 hours, the coagulated polymer was thawed, washed with demineralised water and dried at 80° C. for 48 hours.

[0070] (Comparative) Example of Suspension Polymerization - Method CM3 Example 4C - Copolymer VDF-TrFE at 70 / 30 (molar ratio) Into a vertical autoclave made of AISI 316 steel and an agitator operating at 880 rpm, 1406 g of demineralized water were introduced. When a temperature of 14° C. was reached, 664 g of VDF, 358 g of TrFE, 713 g of an aqueous Ca(OH)2 solution having a concentration of 0.12% w / w, 26.5 g of an aqueous Bermocoll® E230G solution having a concentration of 20 g / kg, 3.11 g of a diethyl peroxydicarbonate solution prepared as described in Example 1 of US Pat. No. 6,255,520 (SOLVAY SA) 3 / 07 / 2001, and 8.3 g of diethylene carbonate were introduced. The temperature was then increased to 40° C. and a pressure of 80 absolute bar was reached. The reaction was continued at 40° C. until the pressure had dropped to 44 absolute bar, then the temperature was increased to 55° C. and kept at this setting until the pressure had dropped to 29 absolute bar; the temperature was increased again to 60° C. and kept at this setting until the pressure had dropped to 8 absolute bar. At this point, the reactor was allowed to cool at room temperature and vented. The obtained polymer was washed with demineralized water and dried at 100° C. for 16 hours.

[0071] Example 12C - Copolymer VDF-TrFE at 75 / 25 (molar ratio) The same procedure was followed as in Example 4C, but initially 767 g VDF and 255 g TrFE were charged and the polymerization was continued in the final step at 60° C. until the pressure had dropped to 7 absolute bar.

[0072] The monomer composition and basic properties of the obtained polymers are summarized in the table below.

[0073] TIFF0007612328000015.tif153170

[0074] TIFF0007612328000016.tif143170

[0075] (*)T c , ΔH c , T m and ΔH mare the Curie transition temperature, the enthalpy associated with the Curie transition, the melting temperature, and the enthalpy of fusion, respectively, determined by differential scanning calorimetry according to ASTM D3418 and ASTM D3418. (§) Xc is a parameter: TIFF0007612328000017.tif20161(#)Mw is the weight average molecular weight determined by GPC against polystyrene as the standard using dimethylacetamide as the solvent.

[0076] Thermal property measurements (j) Curie transition temperature (T C ) and the enthalpy associated with the Curie transition (ΔH c ) Measurement T c Or Curie transition temperature represents the temperature at which a transition between ferroelectric and paraelectric phases occurs in a ferroelectric material. The Curie transition temperature is determined as the first endothermic peak appearing in the DSC thermogram during the second heating cycle, or understood according to the ASTM D 3418 standard. ΔH c is the enthalpy associated with this first order transition (Curie transition) and is determined in the second heating cycle of the DSC thermogram as detailed above, and the instructions contained in the ASTM D 3418 standard apply mutatis mutandis to the first endothermic peak appearing in said second heating cycle, with modifications as necessary. DSC analyses were performed using a Perkin Elmer Diamond DSC instrument, employing a heating rate of 10° C. / min in the second heating cycle as specified in ASTM D 1238.

[0077] (jj) Enthalpy of fusion (ΔH m ) and melting temperature (T m ) Measurement The enthalpy of fusion (ΔH m ) and melting temperature (T m ) is required.

[0078] Piezoelectric measurements (i) Preparation of films Polymer solutions at a concentration of 20% w / w in methyl ethyl ketone were prepared and films were cast onto glass substrates by doctor blade technique using an Elcometer Automatic Film Applicator, Model 4380.

[0079] The polymer layer thus cast was dried under vacuum at 100° C. for 2 hours. On the film thus obtained and dried, 12 patterns of 1 cm×1 cm were printed as electrodes on both sides of the polymer film by inkjet printing technique using poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) purchased by Agfa-Gevaert under the trade name ORGACON® as conductive material. The thickness of the sample was measured using a Mitutoyo micrometer.

[0080] (ii) Annealing of the film The film obtained as detailed above was placed in a vented oven set at an internal temperature of 135° C. After 1 hour, the oven was switched off and allowed to cool to room temperature for 5 hours.

[0081] (iii) Film poling The films were poled using an LC Precision poling device coupled with a High Volate Interface with a RADIANT generating an electric field of up to 10 KV. The annealed films were placed in a polarization cell where an electric field of 150 V / micron or 200 V / micron was applied across the annealed specimen.

[0082] (iv) Measurement of piezoelectric coefficient (d33) The piezoelectric coefficient (d33) values ​​were measured using a PIEZOMETER PM300 instrument by placing the poled samples obtained above in the strain gouges of the instrument to induce the film at room temperature under vibration of 110 Hz. d33 is reported as μC / N.

[0083] (v) Leakage measurement at 100V / μm Leakage refers to the gradual loss of energy from a charged capacitor. Leakage measurements are performed with a polarization cell that applies 100V / micron to the electrodes of a capacitor and measures the energy loss after 5 seconds.

[0084] (vi) Measurement of the dielectric constant of the film The values ​​of the dielectric constant [k] were derived from direct measurements of the dielectric capacitance with a piezometer system provided by Piezotest. All capacitance values ​​were measured at 110 Hz. TIFF0007612328000018.tif20161

[0085] (vi) Ferroelectric hysteresis measurement (P r , P max ) Hysteresis measurements were performed by poling the annealed films with electric fields ranging from 80 V / micron to 250 V / micron to obtain hysteresis curves from which the maximum and remnant polarizations were determined. max is the maximum polarization that can be achieved with the maximum applied electric field, and P r is the residual polarization (also called remnant polarization) in the sample after the applied electric field is removed.

[0086] The results are summarized in the table below.

[0087] TIFF0007612328000019.tif150170

[0088] TIFF0007612328000020.tif125170

[0089] TIFF0007612328000021.tif125170

[0090] For a meaningful comparison, the collected data are organized in Table 4 to allow ready comparison between a group of VDF-TrFE copolymers with roughly similar monomer compositions but different preparation methods.

[0091] Thus, comparing the piezoelectric properties of VDF / TrFE copolymers with a composition of substantially 70 / 30 mol / mol (see examples 1; 2c; (3c); 4c), where example 1 is a copolymer obtained from a latex according to the invention, 2c and 3c are obtained from latexes polymerized in the presence of alternative surfactants, but which do not achieve the claimed ordered crystalline structure; and example 4C is a copolymer from suspension polymerization, it is found that the values ​​of remnant polarization (P r ) was achieved in Example 1 for Examples 2c and 3c, and nearly identical values ​​were obtained for suspension polymerized 4c.

[0092] In fact, remnant polarization (P r ) is a parameter that identifies a material's ability to continue to elongate its crystals after poling and is one of the most important measurable properties for determining piezoelectric performance.

[0093] Similarly, a comparison of Examples 5 and 6 (polymerized from a latex according to the invention in the presence of a cyclic compound) with Example 7C, which is of similar composition but is obtained from a latex polymerized in the presence of an alternative surfactant and does not achieve the structural order in the crystalline phase claimed herein, reveals a higher P r , higher P max and higher d 33 The effectiveness of providing value is demonstrated.

[0094] The same conclusion can again be drawn when considering the performance of Example 8 obtained from a latex according to the invention, which exceeds the performance of Examples 10c, 11c (obtained from an emulsion polymerized latex, not according to the invention) and Example 12C (from a suspension polymerized material): in this case, for a composition of 75 / 25 mol / mol, the remnant polarization value P achieved with the polymer obtained from the latex according to the invention is 1.25 times that of the Example 8 obtained from a latex according to the invention. r and d33 The values ​​are not only superior to the performance achieved with other emulsion polymerized copolymers, but also exceed the performance achieved by suspension polymerization.

Claims

1. An aqueous latex comprising polymer particles [polymer (F)] comprising: The polymer (F) repeat units derived from vinylidene fluoride (VDF) in an amount of 65 to 82 mol %, based on the total moles of repeat units; and repeating units derived from trifluoroethylene (TrFE) in an amount of 18 to 35 mol %, based on the total moles of repeating units It consists of: The polymer (F) has a thermodynamically ordered structure in a ferroelectric phase: (i) A parameter Xc (%) defined as follows: [In the formula, ΔH c is the enthalpy associated with the Curie transition between the ferroelectric and paraelectric phases, determined in J / g in the second heating scan by DSC at a heating rate of 10° C., and ΔH m is the enthalpy of fusion determined in J / g according to ASTM D3418; (ii) the content of repeat units different from VDF, expressed in mol % relative to the total moles of repeat units, the content referred to as CM (mol %); and The relationship is the following inequality: Xc(%)≧a·CM(mol%)+b (wherein a=−1.10 and b=75.00). Meet the water-based latex.

2. 2. The aqueous latex according to claim 1, wherein the melt flow index (MFI) of said polymer (F) is from 0.5 to 500 g / 10 min, measured according to ASTM D1238 (230° C. / 5 kg).

3. 3. A method for making the latex of claim 1 or 2, the method comprising: mixing vinylidene fluoride (VDF) and trifluoroethylene (TrFE) in an aqueous emulsion with a radical initiator and a compound of formula (I): [wherein X are equal or different from each other] 1 , X 2 , X 3 C independently contains H, F, and optionally one or more catenary or non-catenary oxygen atoms; 1~6 (per)fluoroalkyl groups; L represents a bond or a divalent group; R F is a divalent fluorinated C 1~3 is a bridging group; and Y is an anionic functional group. A method for producing a latex, comprising a step of polymerizing in the presence of a fluorinated surfactant [surfactant (C)] that satisfies the above.

4. In the formula (I), the anionic functional group Y is represented by the formula: (In the formula, X a is H, a monovalent metal or a group of the formula -N(R' n ) 4 where R' is equal or different at each occurrence. n is a hydrogen atom or C 1~6 represents a hydrocarbon group) 4. The method of claim 3, wherein the latex is selected from the group consisting of:

5. The method for preparing a latex according to claim 4, wherein the hydrophilic functional group Y is a carboxylate of the formula (3″) detailed in claim 4.

6. The cyclic fluoro compound is represented by the following formula (II): [wherein X are equal or different from each other] 1 , X 2 , X 3 C independently contains H, F, and optionally one or more catenary or non-catenary oxygen atoms; 1~6 (per)fluoroalkyl groups; R F is a divalent fluorinated C 1~3 Y is a bridging group; (In the formula, X a is H, a monovalent metal or a group of the formula -N(R' n ) 4 where R' is equal or different at each occurrence. n is a hydrogen atom or C 1~6 represents a hydrocarbon group) is a carboxylate of The method for producing a latex according to claim 5, which satisfies the above.

7. The cyclic fluoro compound is represented by the following formula (IV): [In the formula, R F is a divalent fluorinated C 1~3 is a bridging group, and Xa is H, a monovalent metal or a group of the formula -N(R' n ) 4 where R' is equal or different at each occurrence. n is a hydrogen atom or C 1~6 are hydrocarbon groups; X are equal or different * 1 , X * 2 are independently a fluorine atom, -R' f OR' f (where R' f is C 1~3 is a perfluoroalkyl group; R F 1 is F or CF 3 and k is an integer from 1 to 3. The method for producing a latex according to claim 5, which satisfies the above.

8. The cyclic fluoro compound has the formula (V): (In the formula, X a is H, a monovalent metal or a group of the formula -N(R' n ) 4 where R' is equal or different at each occurrence. n is a hydrogen atom or C 1~6 represents a hydrocarbon group) The method for producing a latex according to claim 7, which satisfies the above.

9. A process for preparing a latex according to any one of claims 4 to 8, wherein the polymerization pressure is comprised between 10 and 40 bar and / or the polymerization temperature is chosen in the range between 60 and 120°C.

10. The method for preparing a latex according to any one of claims 4 to 8, wherein the radical initiator is selected from the group consisting of organic radical initiators.

11. The method for preparing a latex according to any one of claims 4 to 9, wherein the radical initiator is selected from the group consisting of inorganic radical initiators.

12. 3. A method for manufacturing an electric / electronic device, said method comprising using the latex according to claim 1 or 2 as a ferroelectric, piezoelectric, dielectric or current collecting material in said electric / electronic device.

Citation Information

Patent Citations

  • Polymers containing vinylidene fluoride and trifluoroethylene

    JP2011522096A

  • Method for producing fluoropolymers

    JP2011527362A

  • Method for producing fluoroelastomers

    JP2013514415A